2006
DOI: 10.1097/01.icl.0000174756.54836.98
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Contact Lens Wear on the Ocular Surface Changes in Keratoconus

Abstract: The ocular surface changes in keratoconus may be directly related to contact lens wear and not to the keratoconic shape itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
0
19
0
2
Order By: Relevance
“…This difference affects the fitting of the bevel area, with a decrease in bevel width being apparent by slit lamp observation with fluorescein staining. In severe cases of keratoconus, the peripheral cornea in the flatter meridian direction makes marked contact with the edges of the lens, often resulting in the development of corneal epithelial disorders [25]. Such inadequate fitting also reduces tear volume under the lens at the bevel zone and results in a sensation of discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…This difference affects the fitting of the bevel area, with a decrease in bevel width being apparent by slit lamp observation with fluorescein staining. In severe cases of keratoconus, the peripheral cornea in the flatter meridian direction makes marked contact with the edges of the lens, often resulting in the development of corneal epithelial disorders [25]. Such inadequate fitting also reduces tear volume under the lens at the bevel zone and results in a sensation of discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…10 Progression of KC is often concurrent with contact lens wear, 11 and local tear film alterations (see Section III) could be related to contact lens wear rather than KC alone. 12 In contrast, contact lens wear was not associated with progressive KC in a longitudinal study, and a cause-effect relationship cannot be drawn on cross-sectional data. 11,13 Proteomic studies revealed dysfunctional levels of proteinases, immunoglobulins, epithelial proteins, and factors associated with collagen homeostasis.…”
Section: Introductionmentioning
confidence: 90%
“…12 Indeed, keratoconic eyes have a damaged ocular surface suffering from the consequences of inadequate tear and mucin production, as well as aberrant antioxidant status and proteome alterations that affect tear fluid stability and quality. [93][94][95][96][97] Thus, the affected ocular M A N U S C R I P T…”
Section: Inflammatory Mediators In Tear Fluid Of Patients With Kmentioning
confidence: 99%
“…A adaptação com o desenho tipo Soper visa principalmente evitar ou minimizar o toque apical. As alterações na distribuição dos diferentes padrões da relação LC X córnea, observadas nos dois grupos, podem refletir mudanças topográficas da córnea relacionadas com a evolução do cone, com a filosofia de adaptação das LC ou, simplesmente, serem conseqüências do uso contínuo das mesmas, já que estudos comprovaram que no ceratocone a resistência do tecido corneal e a rigidez escleral são mais baixas que o normal (28)(29)(30) . Outras causas para as variações do padrão fluoresceínico, encontradas entre a 1ª visita e o exame final, podem ter sido a dificuldade de reprodutibilidade do padrão fluoresceínico pela variedade da concentração e quantidade de fluoresceína instilada; as mudanças químicas e físicas da lágrima (osmolaridade, pH, viscosidade, concentração protéica); a movimentação e o posicionamento da LC; e as forças externas relacionadas à compressão, ao posicionamento e à mobilidade das pálpebras (31)(32)(33)(34)(35) .…”
Section: Resultsunclassified
“…Embora existam relatos que a causa da deformação da córnea pela LC relaciona-se principalmente com alterações fisiológicas associadas com longo tempo de hipóxia (39)(40) , o material das LC usadas neste estudo tinham Dk/L suficiente para evitar hipóxia, além de terem sido removidas para dormir. As LC RGP são capazes de induzir mecanicamente alterações na topografia corneal de olhos sadios (30,(41)(42) e muito mais nos olhos portadores de ceratocone (28)(29) . Por isso, as alterações topográficas observadas, embora possam refletir mudanças de curvatura da córnea relacionadas com a evolução do cone, considerando-se o período de acompanhamento dos pacientes podem ser creditadas, na maior parte, ao uso das LC.…”
Section: Resultsunclassified